Implementation of patient and public involvement and engagement (PPIE) for the therapies for long COVID in non-hospitalised individuals (TLC) project - Olalekan Lee Aiyegbusi; Christel McMullan; Sarah E. Hughes; Grace M. Turner; Shamil Haroon; Richard Hotham; Kirsty Brown; Yvonne Alder; Lisa Agyen; Lewis Buckland; Jennifer Camaradou; Amy Chong; et al. (Research Involvement and Engagement)
Abstract Background Patients, their family members and caregivers have firsthand experiences of living with or supporting someone living with a disease or medical condition. This knowledge by experience cannot be replaced by the knowledge acquired by clinicians, researchers, or other professionals through study and/or work. The Therapies for Long COVID in non-hospitalised individuals (TLC) research project was funded in the UK by the National Institute for Health and Care Research (NIHR) and UK Research and Innovation to investigate the impact of long COVID on affected individuals. This article focuses on the implementation of PPIE for the TLC project. It provides details on the methodological approach that was adopted, the evaluation and reporting of the PPIE for the project and some previously unreported challenges we faced. Main body A PPIE Lead was appointed to coordinate PPIE for the project and facilitate communication and relationship building with the patient partners. Our overarching approach was collaborative with patient partners actively involved in the various work packages of the project.. This was achieved by recruiting PPIE members from (1) direct contacts, (2) long COVID support groups (3) a local general practitioner (GP) surgery. Although we were unable to hold face-to-face meetings due to the social restrictions during the COVID-19 pandemic, we offered patients the choice of using virtual platforms like Zoom, telephone calls, and emails for communication. We adopted a 4-tiered model for the PPIE group with each tier providing different opportunities for contributing to the project. This model helped the PPIE Lead to effectively co-ordinate PPIE activities for the project as well as provide all patient partners the opportunity to contribute to the project whilst managing their condition. PPIE for the TLC project was co-evaluated with patient partners. Conclusions Despite the challenges we encountered with the pandemic, the TLC project provided a valuable opportunity for patients to shape the design, conduct and dissemination of the research findings. The information provided in this article may be useful to other researchers and patients when planning PPIE for future health research. The implementation of PPIE in healthcare research could help ensure that the outcomes of research are those valued by and relevant to the needs of patients and other end users.